Mammary Tumorigenesis and Metabolome in Male Adipose Specific Monocyte Chemotactic Protein-1 Deficient MMTV-PyMT Mice Fed a High-Fat Diet - Yan, Lin; Sundaram, Sneha; Rust, Bret M.; Picklo, Matthew J.; Bukowski, Michael R. (Frontiers in Oncology, 2021)
Male breast cancer, while uncommon, is a highly malignant disease. Monocyte chemotactic protein-1 (MCP-1) is an adipokine; its concentration in adipose tissue is elevated in obesity. This study tested the hypothesis that adipose-derived MCP-1 contributes to male breast cancer. In a 2x2 design, male MMTV-PyMT mice with or without adipose-specific Mcp-1 knockout [designated as Mcp-1-/- or wild-type (WT)] were fed the AIN93G standard diet or a high-fat diet (HFD) for 25 weeks. Mcp-1-/- mice had lower adipose Mcp-1 mRNA expression than WT mice. Adipose Mcp-1 deficiency reduced plasma concentrations of MCP-1 in mice fed the HFD compared to their HFD-fed WT counterparts. Mcp-1-/- mice had a longer tumor latency (25.2 weeks vs. 18.0 weeks) and lower tumor incidence (19% vs. 56%), tumor progression (2317% vs 4792%), and tumor weight (0.23 g vs. 0.64 g) than WT mice. Plasma metabolomic analysis identified 56 metabolites that differed among the four dietary groups. Discriminant analysis along with pathway and network analyses showed that amino acid metabolism (alanine, isoleucine, leucine, phenylalanine, threonine, and valine) and carbohydrate metabolism (fumaric acid, glucuronic acid, hexuronic acid, and malic acid) are the most disturbed in MMTV-PyMT mice. In conclusion, adipose-derived MCP-1 may contribute to mammary tumorigenesis in male MMTV-PyMT mice through perturbation of amino acid and carbohydrate metabolism.